2016
DOI: 10.3140/bull.geosci.1594
|View full text |Cite
|
Sign up to set email alerts
|

Lower Lochkovian (Lower Devonian) conodonts from Cellon section (Carnic Alps, Austria)

Abstract: The conodont stratigraphy of the lower Lochkovian part of the famous Cellon section is presented. The association includes twenty-two taxa belonging to nine genera, and allows discriminating the two biozones of the lower Lochkovian (Icr. hesperius and Icr. postwoschmidti zones). Three taxa (Zieglerodina formosa, Z. mashkovae and Z. prosoplatys) are reported for the first time from the Carnic Alps, and other two species of Zieglerodina, probably new, are described in open nomenclature.•

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
0
16
0
3
Order By: Relevance
“…There are many regions where the Silurian-Devonian boundary has been documented: Australia -New South Wales and Victoria (Garratt & Wright 1988, Packham et al 2001, Vérard 2009; Argentine -Precordillera (García Muro et al 2014); Algeria (Kermandji 2007); Canada -Canadian Arctic islands, Ontario and Yukon Territory (Lenz 1968(Lenz , 1982(Lenz , 1988Telford 1988;Märss et al 1998); China -Yunnan Province and Guangxi Province (Zhao & Zhu 2010Zhao et al 2015); England (Holland & Richardson in Martinsson et al 1977); Greenland (Blom 1999); Germany -Frankenwald (Carls et al 2007); Italy -Carnic Alps and Sardinia (Corriga & Corradini 2009;Corradini & Corriga 2010, 2012Corriga et al 2016); Kazakhstan (Bandaletov & Mikhajlova 1971); Libya (Rubinstein & Steemans 2002); Morocco -AntiAtlas (Crick et al 2001, Lubeseder 2008, Corriga et al 2014; Mexico -Sonora (Boucot et al 2008); Poland -Bardzkie Mountains (Porębska & Sawłowicz 1997); Russia -South Urals (Mavrinskaya & Slavík 2013); Spain -East Iberian Chains and Guadarrama (Carls in Martinsson 1977); Turkey -Hazro Area (Kranendonck 2004); Thailand (Burret et al 1986); USA -Alaska (Blodgett et al 1988), Nevada (Klapper & Murphy 1975, Murphy & Matti 1982, Appalachian Mountains (Saltzman 2002); Ukraine -Podolia (Paris & Grahn 1996;Drygant & Szaniawski 2009, 2012…”
Section: Silurian-devonian Boundary -Historical Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many regions where the Silurian-Devonian boundary has been documented: Australia -New South Wales and Victoria (Garratt & Wright 1988, Packham et al 2001, Vérard 2009; Argentine -Precordillera (García Muro et al 2014); Algeria (Kermandji 2007); Canada -Canadian Arctic islands, Ontario and Yukon Territory (Lenz 1968(Lenz , 1982(Lenz , 1988Telford 1988;Märss et al 1998); China -Yunnan Province and Guangxi Province (Zhao & Zhu 2010Zhao et al 2015); England (Holland & Richardson in Martinsson et al 1977); Greenland (Blom 1999); Germany -Frankenwald (Carls et al 2007); Italy -Carnic Alps and Sardinia (Corriga & Corradini 2009;Corradini & Corriga 2010, 2012Corriga et al 2016); Kazakhstan (Bandaletov & Mikhajlova 1971); Libya (Rubinstein & Steemans 2002); Morocco -AntiAtlas (Crick et al 2001, Lubeseder 2008, Corriga et al 2014; Mexico -Sonora (Boucot et al 2008); Poland -Bardzkie Mountains (Porębska & Sawłowicz 1997); Russia -South Urals (Mavrinskaya & Slavík 2013); Spain -East Iberian Chains and Guadarrama (Carls in Martinsson 1977); Turkey -Hazro Area (Kranendonck 2004); Thailand (Burret et al 1986); USA -Alaska (Blodgett et al 1988), Nevada (Klapper & Murphy 1975, Murphy & Matti 1982, Appalachian Mountains (Saltzman 2002); Ukraine -Podolia (Paris & Grahn 1996;Drygant & Szaniawski 2009, 2012…”
Section: Silurian-devonian Boundary -Historical Overviewmentioning
confidence: 99%
“…Spathognathodontid conodonts are abundant in strata around the Silurian-Devonian boundary. They have been described from many areas: e.g., Australia -Queensland, New South Wales (Simpson 2000, Farrell 2004); Austria -Carnic Alps (Suttner 2009); Baltica -Lithuania (Spiri donov 2020); Czech Republic -Prague Synform (Walliser 1964, Schönlaub in Chlupáč et al 1980, Kříž et al 1986, Carls et al 2007, Slavík 2011, Hušková & Slavík 2020; Germany -Frankenwald (Carls et al 2007); Italy -Carnic Alps and Sardinia (Walliser 1964;Corradini 2007;Corriga & Corradini 2009;Corradini & Corriga 2010, 2012Corriga et al 2016;Schönlaub et al 2017); Mexico -Sonora (Boucot et al 2008); Morocco -AntiAtlas (Corriga et al 2014); Pakistan -Peshawar Basin (Mawson et al 2003); Spain -East Iberian Chains and Guadarrama (Carls in Martinsson 1977); USA -Alaska (Blodgett et al 1988), Nevada (Klapper & Murphy 1975, Murphy & Matti 1982), New York (Kleffner et al 2009); Ukraine -Podolia (Drygant & Szaniawski 2009, 2012; Russia -South Urals (Mavrinskaya & Slavík 2013). Data from sections from Austria, Czech Republic, Germany, Missouri, and Nevada were incorporated into the novel taxonomic concept of Spathognathodontidae by Murphy et al (2004), who reclassified many spatho gna tho dontid taxa and established new genera.…”
Section: Paleogeographic Distribution Of Spathognathodontid Conodontsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the scheme by Corradini and Serpagli (1999) was utilized for the Wenlock, as the detailed subdivision of the Wenlock by Cramer et al (2011) revealed to be unfitting for the Carnic Alps, as already pointed out by Corradini et al (2016). The zonation schemes provided by Corradini and Corriga (2012) and Valenzuela-Ríos et al (2015) are applied for the Lochkovian, with the variations suggested by Corriga et al (2016) in the lower Lochkovian. Finally, the scheme by Slavík (2004) is adopted for the lower Pragian.…”
Section: Conodont Biostratigraphymentioning
confidence: 99%
“…Barrick et al 2005;Corriga 2011;Corriga et al 2011Corriga et al , 2012Slavík et al 2012;Drygant & Szaniawski 2012;Mavrinskaya & Slavík 2013), presenting data that can help in the reconstruction of the phylogenesis of Lanea and Ancyrodelloides (Fig. 7).…”
Section: Phylogenesis Of Genera Lanea and Ancyrodelloidesmentioning
confidence: 99%